Dynamic multilayer routing schemes in GMPLS-based IP+optical networks. - Oki, Eiji.
This article presents two dynamic multilayer routing policies implemented in the photonic MPLS router developed by NTT for IP+optical generalized MPLS networks. According to IP traffic requests, wavelength paths called lambda label switched paths are set up and released in a distributed manner based on GMPLS routing and signaling protocols. Both dynamic routing policies first try to allocate a newly requested electrical path to an existing optical path that directly connects the source and destination nodes. If such a path is not available, the two policies employ different procedures. Policy 1 tries to find available existing optical paths with two or more hops that connect the source and destination nodes. Policy 2 tries to establish a new one-hop optical path between source and destination nodes. The performances of the two routing policies are evaluated. Simulation results suggest that policy 2 outperforms policy 1 if p is large, where p is the number of packet-switching-capable ports; the reverse is true only if p is small. We observe that p is the key factor in choosing the most appropriate routing policy. We also describe items that need to be standardized in the IETF to effectively achieve multilayer traffic engineering.
Keywords: GMPLS-based network; IP network; IP traffic; Dynamic multilayer routing scheme; Generalized multiprotocol label switching; Lambda label switched path; Multilayer routing; Multilayer traffic engineering; One-hop optical path; Optical network; Signaling protocol